The Role of Instruction, Rate and Route in Second Language Acquisition - Novasyari, Ressy (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2022)
In this globalization era, English has become a big issue around the English Foreign Learners (EFL). Many people need to use English as tool to communicate with other people from the world as it is considered that English is an international language. Language is the method of expressing ideas and emotions in the form of signs and symbols. These signs and symbols are used to encode and decode the information. There are many languages spoken in the world. The first language learned by a baby is his or her mother tongue. It is the language, which he or she listens to from his or her birth. Any other language learned or acquired is known as the second language. This paper discusses three aspects in second language acquisition. The first is instruction, the second is rate, and the third is route.